Problematika dan Gerakan Islam Modern (Studi Teks Kitab Musykilat Ad-Da’wah Wa Ad-Da’iyah Karya Fathi Yakan) - Al Fiatur Rohmaniah; Sifa Ahmad Sodiqin; Fatimatuz Zahroul Batul (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2022)
Da'wah is an inseparable part of the history of Islamic development. By explaining the problems of da'wah and the importance of solving problems, it will be an effort to convey advice which in fact is the obligation of every Muslim to Allah, His Book, His Apostle, leaders and Muslims in general. A da'I is needed to help and provide services to the community according to the limits of his ability. Through the Qur'an and Sunnah we can determine the various demands that must be met by a da'i to attract the object of da'wah or mad'u. The researcher uses a text study approach to examine the problems and movements of modern Islam in an Arabic book, namely the book Musykilat Ad-Da'wah Wa Ad-Da'iyah by Fathi Yakan.